2022
DOI: 10.1111/psyp.14203
|View full text |Cite
|
Sign up to set email alerts
|

Neural timing of the other‐race effect across the lifespan: A review

Abstract: Face race influences the way we process faces, so that faces of a different ethnic group are processed for identity less efficiently than faces of one's ethnic group ‐ a phenomenon known as the Other‐Race Effect (ORE). Although widely replicated, the ORE is still poorly characterized in terms of its development and the underlying mechanisms. In the last two decades, the Event‐Related Potential (ERP) technique has brought insight into the mechanisms underlying the ORE and has demonstrated potential to clarify i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 368 publications
(1,137 reference statements)
0
6
0
Order By: Relevance
“…Indeed, at 60% and 100% coherence levels, a very early P1 effect was observed, with higher amplitudes for other- than same-race faces ( Figures 9 and 10 ). While the P1 is an inconsistent index of race processing (see Serafini and Pesciarelli, 2023 for review), some studies have found an enhancement for other-race faces ( Anzures and Mildort, 2021 ), and have been interpreted as reflecting differences in how people process configural information in same- and other-race faces ( Hahn et al. , 2012 ; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, at 60% and 100% coherence levels, a very early P1 effect was observed, with higher amplitudes for other- than same-race faces ( Figures 9 and 10 ). While the P1 is an inconsistent index of race processing (see Serafini and Pesciarelli, 2023 for review), some studies have found an enhancement for other-race faces ( Anzures and Mildort, 2021 ), and have been interpreted as reflecting differences in how people process configural information in same- and other-race faces ( Hahn et al. , 2012 ; Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2020 ), with others reporting no P1 modulation of race at all ( Senholzi and Ito, 2013 ; Vizioli et al. , 2010a , b , see Serafini and Pesciarelli, 2023 for review.) In a mixed result, He et al.…”
Section: Introductionmentioning
confidence: 99%
“…These results show that the classification of faces at the level of race comes at the expense of recognizing faces at an individual person level. At the neural level, the primary and subordinate level processing of own‐ and other‐race faces are characterized by the different event‐related potentials brain components (N170 and N250; Serafini & Pesciarelli, 2022) and in neuroimaging, differential activation of the OFA and FFA brain regions (Ficco et al, 2022).…”
Section: The Expertise Of Own‐race Face Recognitionmentioning
confidence: 99%
“…The other-race effect (ORE) is one possible mechanism contributing to the development of implicit racial bias (Lee et al, 2017 ; Quinn et al, 2018 , 2019 ). The ORE is a perceptual phenomenon whereby individuals process faces of other races less efficiently and have poorer recognition of other-race faces compared to faces of their own racial identity (Kelly et al, 2007 ; Rhodes and Baron, 2019 ; Serafini and Pesciarelli, 2022 ). The ORE emerges in infancy, but the strength of the effect may depend on early individual experience with faces of diverse races and ethnicities (Sangrigoli and De Schonen, 2004 ; Sangrigoli et al, 2005 ; Bar-Haim et al, 2006 ; Heron-Delaney et al, 2011 ; Spangler et al, 2013 ; Sugden, 2016 ; Tham et al, 2019 ; Zhou et al, 2019 , 2022 ; Hwang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…General limitations of infant research impact the current scarcity of literature in this area, including difficulty accessing infant populations and high rates of data loss. Both behavioral and neural studies of the ORE additionally lack sample diversity, particularly for Black, Hispanic/Latino, or Indigenous populations (Serafini and Pesciarelli, 2022 ). Of the infant ORE studies reviewed here, 12 included homogenous samples of White infants (Sangrigoli and De Schonen, 2004 ; Kelly et al, 2005 , 2007 ; Heron-Delaney et al, 2011 ; Spangler et al, 2013 ; Macchi Cassia et al, 2014 ; Fassbender et al, 2016 ; Quinn et al, 2016 ; Krasotkina et al, 2020 ; Hillairet de Boisferon et al, 2021 ; Clerc et al, 2022 ; Damon et al, 2022 ), four included homogenous samples of East Asian infants (Kelly et al, 2009 ; Liu et al, 2015 ; Tham et al, 2019 ; Ujiie et al, 2021 ), and only three included any Black, Hispanic, or bi-/multi-racial infants (Bar-Haim et al, 2006 ; Sugden, 2016 ; Hwang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%